Minimizing error in robot arm based on design optimization for high stiffness to weight ratio - Ali, Ahmed Abdul Hussain (Al-Khwarizmi Engineering Journal, 2008)
In this work the effect of choosing tri-circular tube section had been addressed to minimize the end effector’s error, a comparison had been made between the tri-tube section and the traditional square cross section for a robot arm, the study shows that for the same weight of square section and tri-tube section the error may be reduced by about 33%. A program had been built up by the use of MathCAD software to calculate the minimum weight of a square section robot arm that could with stand a given pay load and gives a minimum deflection. The second part of the program makes an optimization process for the dimension of the cross section and gives the dimensions of the tri-circular tube cross section that have the same weight of the corresponding square section but with less deflection.